Gadora

answers: 1

Register to add an answer

The time for answering the question is over

351 cents

Answer:

x

2

−7x+12

3x

2

−x−2

÷

x

2

−4

3x

2

−7x−6

(∵

B

A

÷

D

C

=

B

A

×

C

D

) and A

2

−B

2

=(A−B)(A+B)

⇒

x

2

−7x+12

3x

2

−x−2

×

3x

2

−7x−6

x

2

−4

⇒

(x−3)(x−4)

(3x+2)(x−1)

×

(3x+2)(x−3)

(x−2)(x+2)

⇒

(x−3)

2

(x−4)

(x−1)(x−2)(x+2)

.

336

gauge

For answers need to register.

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions